2020
DOI: 10.1186/s12864-020-6644-7
|View full text |Cite
|
Sign up to set email alerts
|

Systematic analysis of the basic/helix-loop-helix (bHLH) transcription factor family in pummelo (Citrus grandis) and identification of the key members involved in the response to iron deficiency

Abstract: Background: Iron (Fe) deficiency is a common problem in citrus production. As the second largest superfamily of transcription factors (TFs), the basic/helix-loop-helix (bHLH) proteins have been shown to participate in the regulation of Fe homeostasis and a series of other biological and developmental processes in plants. However, this family of members in citrus and their functions in citrus Fe deficiency are still largely unknown. Results: In this study, we identified a total of 128 CgbHLHs from pummelo (Citr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 65 publications
(98 reference statements)
2
25
0
Order By: Relevance
“…In iron-restricted environments, the expression of bHLH genes, such as AtbHLH29 , is essential for plants to absorb more iron [ 85 ]. bHLH genes also play vital roles in responding to iron-deficient conditions and regulating iron uptake and balance in fruit trees, such as pummelo ( Citrus grandis L.) [ 86 ]. These results provide insights that could enable the improvement of iron absorption and utilization in environments with low iron levels ( Figure 4 ).…”
Section: Roles Of Bhlh Tfs In Plant Stress Tolerancementioning
confidence: 99%
“…In iron-restricted environments, the expression of bHLH genes, such as AtbHLH29 , is essential for plants to absorb more iron [ 85 ]. bHLH genes also play vital roles in responding to iron-deficient conditions and regulating iron uptake and balance in fruit trees, such as pummelo ( Citrus grandis L.) [ 86 ]. These results provide insights that could enable the improvement of iron absorption and utilization in environments with low iron levels ( Figure 4 ).…”
Section: Roles Of Bhlh Tfs In Plant Stress Tolerancementioning
confidence: 99%
“…MYB family genes are mainly involved in various functions such as anthocyanin biosynthesis, morphogenesis and abiotic stress responses, among others (Wang et al 2004). Zhang et al (2020) found that MYB family genes in wheat can mediate host resistance to the fungal pathogen Bipolaris sorokiniana by regulating the SA signaling pathway and defense-related genes. Zhu et al (2017) reported that MYB family genes might play a regulatory role in the responses of the "Starking Delicious" pear cultivar to A. alternata attack.…”
Section: Discussionmentioning
confidence: 99%
“…7). However, various studies have shown that bHLH and ARF TFs play key roles in plant growth, development and stress tolerance, but are not stronly correlated with disease resistance (Zhang et al 2020). Therefore, we will not give more details on these TF families here.…”
Section: Discussionmentioning
confidence: 99%
“…MYB sequences of A. thaliana [64], Vitis vinifera [121], Beta vulgaris [122], and Musa acuminata [123] were subject to KIPEs as baits. bHLH bait sequences were collected from A. thaliana [124], V. vinifera [125], Nelumbo nucifera [126], Citrus grandis [127], M. acuminata [128], and Solanum melongena [129]. WD40 sequences of A. thaliana [130], Triticum aestivum [131], and Setaria italica [132] were collected as bait sequences for the identification of the WD40 protein TTG1.…”
Section: Methodsmentioning
confidence: 99%